2023
DOI: 10.3389/fendo.2023.1134154
|View full text |Cite
|
Sign up to set email alerts
|

Association between abnormal lipid metabolism and tumor

Abstract: Metabolic Reprogramming is a sign of tumor, and as one of the three major substances metabolism, lipid has an obvious impact. Abnormal lipid metabolism is related to the occurrence of various diseases, and the proportion of people with abnormal lipid metabolism is increasing year by year. Lipid metabolism is involved in the occurrence, development, invasion, and metastasis of tumors by regulating various oncogenic signal pathways. The differences in lipid metabolism among different tumors are related to variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 137 publications
(215 reference statements)
0
3
0
Order By: Relevance
“…Consistent with the seminal discovery in 1953 that tumors could synthesize lipids in a manner similar to embryonic tissues, many tumor cells have been found to exhibit a high rate of de novo lipogenesis [ 37 ]. Importantly, clinical observations found that lipid metabolism reprogramming often predicts poorer prognosis in cancer patients [ 38 ], including those affected by hematological malignancies. A large number of lipid droplets that store lipids and cholesterol can be detected in tumor cells, and high lipid droplets and cholesterol esters are nowadays considered indicators of aggressiveness of both solid and hematological cancers [ 38 , 39 ].…”
Section: Lipid Metabolic Vulnerabilities Of MMmentioning
confidence: 99%
“…Consistent with the seminal discovery in 1953 that tumors could synthesize lipids in a manner similar to embryonic tissues, many tumor cells have been found to exhibit a high rate of de novo lipogenesis [ 37 ]. Importantly, clinical observations found that lipid metabolism reprogramming often predicts poorer prognosis in cancer patients [ 38 ], including those affected by hematological malignancies. A large number of lipid droplets that store lipids and cholesterol can be detected in tumor cells, and high lipid droplets and cholesterol esters are nowadays considered indicators of aggressiveness of both solid and hematological cancers [ 38 , 39 ].…”
Section: Lipid Metabolic Vulnerabilities Of MMmentioning
confidence: 99%
“…[14] In addition, dysregulated lipid metabolism has increasingly been recognized as a common property of malignant tumors and is highly correlated with the risk of breast, colon, and prostate cancers. [15][16][17] Different types of cancer may present different circulating lipoprotein profiles. Liu et al indicated the potential ability of high-density lipoprotein (HDL) to promote the proliferation and transformation of NPC cells.…”
Section: Introductionmentioning
confidence: 99%
“…The significance of lipid metabolism extends to the development, of cancer (Li et al, 2023), as cancer cells heavily rely on it to acquire the energy, biofilm constituents, and signaling molecules essential for their proliferation, survival, invasion, and metastasis (Bian et al, 2021). Unlike normal cells, cancer cells undergo a series of modifications in lipid metabolism, which can have a profound impact on the increased efflux of anti-tumor drugs and the modulation of apoptotic signaling pathways.…”
Section: Introductionmentioning
confidence: 99%